Lynching and the Sacred in Latin America. Regarding "The part of Crimes" in 2666 of Roberto (Global Journal of Human-Social Science, 2024)
Abstract not found
Keywords: affective interruptions; lynching; sacrifice; crowd; violence; Roberto Bolaño; 2666